2004
DOI: 10.1083/jcb.200409187
|View full text |Cite
|
Sign up to set email alerts
|

Terminal osteoblast differentiation, mediated by runx2 and p27KIP1, is disrupted in osteosarcoma

Abstract: The molecular basis for the inverse relationship between differentiation and tumorigenesis is unknown. The function of runx2, a master regulator of osteoblast differentiation belonging to the runt family of tumor suppressor genes, is consistently disrupted in osteosarcoma cell lines. Ectopic expression of runx2 induces p27KIP1, thereby inhibiting the activity of S-phase cyclin complexes and leading to the dephosphorylation of the retinoblastoma tumor suppressor protein (pRb) and a G1 cell cycle arrest. Runx2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
200
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(212 citation statements)
references
References 56 publications
(82 reference statements)
11
200
1
Order By: Relevance
“…(24) Interactions of RUNX2 with TLE or YAP1 seem not to be involved in repression of the p21 promoter (23,26) Since p21, p27, and p57 are three cyclin kinase inhibitors (CKIs) that belong to the CIP/KIP family, by using osteoprogenitor cells, Drissi and colleagues (27) demonstrated that (1) p27 plays an important role in regulating osteoblast differentiation by controlling proliferation events and (2) ectopic expression of RUNX2 induced p27. (9) . Recently, reduced proliferation and increased apoptosis in bone marrow MSCs were associated with upregulation of p27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) Interactions of RUNX2 with TLE or YAP1 seem not to be involved in repression of the p21 promoter (23,26) Since p21, p27, and p57 are three cyclin kinase inhibitors (CKIs) that belong to the CIP/KIP family, by using osteoprogenitor cells, Drissi and colleagues (27) demonstrated that (1) p27 plays an important role in regulating osteoblast differentiation by controlling proliferation events and (2) ectopic expression of RUNX2 induced p27. (9) . Recently, reduced proliferation and increased apoptosis in bone marrow MSCs were associated with upregulation of p27.…”
Section: Discussionmentioning
confidence: 99%
“…(7) The involvement of RUNX2 as a regulator of osteoblast proliferation also was consistent with data obtained in other biologic contexts. (8)(9)(10)(11) More recently, Zaidi and colleagues (12) proposed that RUNX2 functions as a tumor suppressor in primary diploid osteoblasts, whereas Eliseev and colleagues (13) suggested that RUNX2 acts as a proapoptotic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Results are expressed as treated over control ratio after correction for b-actin expression. Cells were cultured in serum-supporting conditions in all experiments osteosarcoma is associated with reduced Runx2 and Osterix expression whereas overexpressing Runx2 or Osterix induces cell differentiation in osteosarcoma cells, 16,30 an effect that is reproduced by BMP-2. 18 In the present study, Runx2 and phenotypic osteoblast differentiation markers declined under statin treatment, which indicates that statin-induced apoptosis did not occur secondary to cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This strengthens the growing concept that osteosarcoma cell apoptosis can be induced independently of cell differentiation. 18 In addition to promote osteoblast commitment, Runx2 may induce osteoblast growth arrest 13,14 in part through the Cdk inhibitor p27 16 which regulates the transition between proliferation and differentiation in osteoblasts. 13 In that way, loss of Runx2 and p27 expression is associated with disrupted differentiation in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation